2021
DOI: 10.3389/fonc.2021.771335
|View full text |Cite
|
Sign up to set email alerts
|

Various Uses of PD1/PD-L1 Inhibitor in Oncology: Opportunities and Challenges

Abstract: The occurrence and development of cancer are closely related to the immune escape of tumor cells and immune tolerance. Unlike previous surgical, chemotherapy, radiotherapy and targeted therapy, tumor immunotherapy is a therapeutic strategy that uses various means to stimulate and enhance the immune function of the body, and ultimately achieves the goal of controlling tumor cells.With the in-depth understanding of tumor immune escape mechanism and tumor microenvironment, and the in-depth study of tumor immunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 207 publications
1
23
0
Order By: Relevance
“…Thus, PD1/PD-L1 expression can be impacted by regulating many of the aforementioned regulators to improve the response to PD1/PD-L1 inhibitors in patients with or without tumors. In our study, we demonstrated that PD-L1 was significantly declined in unresponsive tumors compared with those that were positive in anti-PD1 responses in HCC patients, which is consistent with a previous study ( 7 ). Additionally, to analyze which genes caused primary drug resistance to anti-PD1 treatment, we sequenced 289 nanostring panel RNA and found increased GUSB expression in the anti-PD1 resistance group, thus finding new predictive molecules and therapeutic targets for anti-PD1 therapy in HCC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, PD1/PD-L1 expression can be impacted by regulating many of the aforementioned regulators to improve the response to PD1/PD-L1 inhibitors in patients with or without tumors. In our study, we demonstrated that PD-L1 was significantly declined in unresponsive tumors compared with those that were positive in anti-PD1 responses in HCC patients, which is consistent with a previous study ( 7 ). Additionally, to analyze which genes caused primary drug resistance to anti-PD1 treatment, we sequenced 289 nanostring panel RNA and found increased GUSB expression in the anti-PD1 resistance group, thus finding new predictive molecules and therapeutic targets for anti-PD1 therapy in HCC.…”
Section: Discussionsupporting
confidence: 93%
“…In the tumor microenvironment, tumor cells and antigen-presenting cells (APCs) upregulate PD-L1 expression to evade immune surveillance through adaptive and internal immune tolerance. Furthermore, the increase in PD-L1 is also a prerequisite for the effectiveness of anti-PD1/PD-L1 monoclonal antibodies ( 7 ). In murine experiments, Juneja et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tumor cells can exploit this mechanism to escape the immune system by upregulating the expression of suppressive molecules that interact with T cells, rendering them incapable of killing [ 27 ]. For example, the binding of PD-L1 expressed by tumor cells to PD-1 on the surface of TILs weakens the immune role of T cells, which causes tumor immune escape and promotes tumor progression [ 40 ]. To date, more than ten types of ICs have been discovered, such as PD-1, PD-L1, cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), T cell immunoglobulin and mucin domain containing-3 (TIM-3), and lymphocyte-activation gene 3 (LAG3/CD223), of which the most extensively studied are CTLA-4 and PD-1/PD-L1.…”
Section: Immune Evasion and Icismentioning
confidence: 99%
“…Through the JAK and STAT signaling pathways, CXCL10-CXCR3 is hypothesized to regulate PD-L1 synthesis in fibroblasts ( 17 ). Activation of PD-L1/PD-1 poses great difficulties for cancer therapy ( 18 ), which is often associated with cytotoxic T lymphocyte malfunction. In patients with gynecologic malignancies, elevated PD-L1 expression may be a useful biomarker for predicting clinical outcomes ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%